PENGEMBANGAN INSTRUMEN KECERDASAN NATURALIS ANAK USIA DINI DI KABUPATEN LUWU TIMUR PROVINSI SULAWESI SELATAN - Affandi Ismail (Jurnal Evaluasi Pendidikan, 2018)
The purpose of this development is to develop instruments Early Childhood Naturalist intelligence in East Luwu Regency South Sulawesi Province, valid and reliable. Operationally, this study is to describe: (1) the development of instruments Naturalist intelligence Childhood and (2) constructing instruments Naturalist intelligence Early Childhood valid and reliable. This study was conducted in 10 public elementary school in East Luwu Regency. Conceptually, construct naturalistic intelligence consists of seven dimensions, namely: (1) Sensitivity to nature, (2) ability to identify, classify and distinguish some species in large quantities, including flora, fauna, and the environment, (3) The food chain, (4 ) Love of nature, animals, and plants, (5) the ability to distinguish living matter with inanimate objects, (6) Interested in the world of animals or plants, and (7) Care about the environment, pay attention to nature and easily adapt to nature. Based on the review and validation expert panelists interrater coefficient values obtained for the seven dimensions is reliable. Data analysis using SEM with 8.80 lisrel software model of first order confirmatory analysis. In the first empirical test validation results are 26 items that drop while in the second stage of empirical testing of all items that as many as 29 items declared valid. Reliability test results construct empirical tests first and second stages shows all dimensions reliable. At GOF size mostly show a good fit (good fit), so the instrument Naturalist intelligence Childhood in East Luwu regency of South Sulawesi Province has developed a valid and reliable and can be used as a measuring tool that is reliable.